2021
DOI: 10.1055/a-1352-2944
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and safety of magnetic sphincter augmentation (MSA) and transoral incisionless fundoplication (TIF2) in refractory gastroesophageal reflux disease (GERD): a systematic review and meta-analysis

Abstract: Background and study aims Proton pump inhibitors (PPI) are effective medical therapy options for gastro-esophageal reflux disease (GERD). However, 20 % to 40 % of patients report symptoms despite taking daily PPI. Transoral incisionless fundoplication (TIF2) and magnetic sphincter augmentation (MSA) are less invasive options for the treatment of refractory GERD and are increasingly gaining popularity. Methods We conducted a comprehensive search of several databases to identify relevant studies. Our p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…While we are not aware of any published direct or randomized comparisons between MSA and transoral incisionless fundoplication, a meta-analysis including 24 studies with 1942 patients found comparable improvements in GERD-HRQoL scores (78–80%), with greater proportions with improvement in regurgitation (91% vs. 73%) and PPI discontinuation (91% vs. 64%) for MSA compared with transoral incisionless fundoplication. 48 …”
Section: Outcomes Compared With Fundoplicationmentioning
confidence: 99%
“…While we are not aware of any published direct or randomized comparisons between MSA and transoral incisionless fundoplication, a meta-analysis including 24 studies with 1942 patients found comparable improvements in GERD-HRQoL scores (78–80%), with greater proportions with improvement in regurgitation (91% vs. 73%) and PPI discontinuation (91% vs. 64%) for MSA compared with transoral incisionless fundoplication. 48 …”
Section: Outcomes Compared With Fundoplicationmentioning
confidence: 99%